Physico-mechanical properties of sugar cane stalks related to mechanical harvesting - Sureshkumar, P.K.; Manohar Jesudas, D. (Journal of Tropical Agriculture, 2015)
A study was under taken to investigate the base cutting and lifting actions of a sugar cane harvester. To obtain preliminary data required for the study, laboratory and field measurements were made to ascertain the cutting and lifting behaviour of sugar cane stalk that can be used by designers for design of the sugar cane harvester. An apparatus was developed to measure the lifting moment of sugarcane stalk from the lodged position to vertical under field conditions. Laboratory studies were conducted to measure the mechanical properties of sugarcane stalk. To measure the cutting energy a pendulum type impact cutting device was used. Flexure test were conducted for measuring the modulus of elasticity. The maximum lifting moment varied from 30.62 Nm to 129.11 Nm and the lifting moment was dependent upon the field conditions and degree of entanglement. The specific cutting energy increased linearly when the oblique angle was increased from 0 to 350 and the specific cutting energy was lowest at a tilt angle of 200 when the oblique angle was 300. The flexure test on sugarcane stalk as a simple supported beam gave Young’s modulus values of 1165.27 to 1667.11 M Pa. The same when loading was done as cantilever beam was 2266.17 to 2905.61 M Pa.